2017
DOI: 10.1007/s10198-017-0884-8
|View full text |Cite
|
Sign up to set email alerts
|

Do healthcare tax credits help poor-health individuals on low incomes?

Abstract: In several countries, personal income tax permits tax credits for out-of-pocket healthcare expenditure. Tax credits benefit taxpayers at all income levels by reducing their net tax liability and modify the price of out-of-pocket expenditure. To the extent that consumer demand is price elastic, they may influence the amount of eligible healthcare expenditure for which taxpayers may claim a credit. These effects influence, in turn, income distributions and taxpayers' health status and therefore income-related in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…More recently, Eggink et al [23] are following a comparable approach to forecast the use of elderly care in the Netherlands. In addition, Di Novi et al [24] are using a static tax-benefit-model to analyze the distributional effects of tax breaks for outof-pocket payments. The third section presents the results of our stochastic microsimulation model and further data analysis showing the contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Eggink et al [23] are following a comparable approach to forecast the use of elderly care in the Netherlands. In addition, Di Novi et al [24] are using a static tax-benefit-model to analyze the distributional effects of tax breaks for outof-pocket payments. The third section presents the results of our stochastic microsimulation model and further data analysis showing the contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of tax-related expenditures in addressing a taxpayer behavioural change is out of the scope of the study, since this would imply the need for information on elasticities for all countries in the very different contexts of housing ownership choices, health and education spending. Morel et al (2019), Branco and Costa (2018) and Di Novi et al (2018) provide interesting examples of country-specific analysis whose extension in a cross-country perspective is hampered by data availability and left for future research developments.…”
Section: Resultsmentioning
confidence: 99%
“…A favourable tax treatment can indeed provide an incentive to low-income individuals to benefit from medical treatments. Overall, these tax provisions supplement benefits provided by government health programmes (see Branco and Costa, 2018, for the case of Portugal and Di Novi et al, 2018, for Italy) and subsidize the cost of private health insurance (Hinde, 2016), reducing the up-front cost of obtaining good health coverage.…”
Section: The Rationale Of Social Tes In the Context Of Personal Incommentioning
confidence: 99%
See 1 more Smart Citation
“…We found only one study that had assessed how income based policies would affect health inequalities. 32 Di Novi and colleagues 32 found that healthcare tax credits in Italy increased inequalities in health status, and that the policy could be redesigned to reduce this effect. Similarly, Griffin and colleagues 33 estimated that almost onethird of the health interventions recommended by the National Institute for Health and Care Excellence were likely to increase health inequalities.…”
Section: Discussionmentioning
confidence: 99%